Sistem Informasi Berbasis Web Penerimaan Siswa Baru Sma Negeri 9 Merangin - Raimon Efendi; Heri Sudibyo; Sepri Rahmat Pratama (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2023)
This research was conducted because the New Student Admission (PSB) still uses a manual recording method using a book, which causes the committee to have to do repetitive recording and tasks, which are sometimes ineffective and time consuming. In fact, data processing of prospective students is also not managed properly. The use of handwritten records will make it difficult for the committee to read them, especially with the increasing number of new student applicants every year. Therefore, the recapitulation and data entry process takes longer to process. The data collection methods used in this research include observation and literature study. While in system development, the Waterfall development method is used. The resulting online PSB information system provides a fairly appropriate solution to reduce existing constraints. This web-based online PSB information system allows access to information anywhere and anytime, because it is based on the web. Thus, every prospective student who wants to register can do so online, overcoming the obstacles and limitations that existed in the previous manual system.